Kekuatan Voice of Customer di Media Sosial: Dampaknya terhadap Respons dan Perbaikan CRM Perbankan - Windarsari, Wiwin Riski; Zaimar, Fina Ruzika; Haruna, Hasisa; Ridha, Achmad; Mangga, Andi Rahmatullah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
Social media is increasingly serving as a primary channel for customers to voice their banking experiences, including complaints, questions, and appreciation. This study aims to analyze the power of Voice of Customer (VoC) on platform X and its impact on company responses and Customer Relationship Management (CRM) improvements. The study analyzed 1,456 posts from 998 unique accounts addressed to Bank C's official account during August 2025. The results showed that dominant complaints included failed transactions with balance deductions, application disruptions, OTP and verification issues, difficulties contacting customer service, and security and fraud issues. Company responses were generally directed to private channels (DM or phone) using template-based answers. However, personalization efforts were evident in innovative application features, such as transaction notifications, e-statements, and the Bank C keyboard. These findings confirm that VoC is not simply a source of complaints but also a strategic input that can drive system improvements and interaction quality. Practical implications include the need to strengthen social listening, improve the quality of personalized responses, and integrate VoC directly into CRM. The use of AI and automation can also support the initial response process, while maintaining human oversight for sensitive cases. This research was limited to a single banking institution, a single platform, and a specific period, so the results cannot be broadly generalized. Future studies are recommended to involve more institutions, communication channels, and take a longitudinal approach to assess the impact of CRM improvements on customer satisfaction and loyalty.